Perfectionism, obsessive-compulsory behaviour, and anxiety in young adults: a moderated mediation model of mobile phone addiction - Jiao Cheng; Yanjun Chen; Jin Liu; Sirui Gao; Yumeng Ju; Bangshan Liu; Zhengzong Liu; Yan Zhang (BMC Public Health)
Abstract Background Mobile phone addiction is becoming a topical concern among young adults. Recent research argues that mobile phone addiction is related to perfectionism, anxiety, and obsessive-compulsory behaviour. Yet, there is a lack of an integrated model encompassing these factors to explain mobile phone addiction. Guided by a moderated mediation framework, the study aimed to investigate whether perfectionism predisposes young adults to mobile phone addiction through obsessive-compulsory behaviour and anxiety. Methods A cross-sectional survey was used to examine all the variables among 1404 Chinese universities’ student. Results The results a prevalence of 56.50% in mobile phone addiction among the participants. The direct association between perfectionism and mobile phone addiction was significant (β = 0.12, 95%CI [0.09, 0.15]). Obsessive-compulsory behaviour partially mediated the relationship between perfectionism and mobile phone addiction (indirect effect = 0.08, 95%CI [0.06, 0.10]). Additionally, as anxiety increased, the association between perfectionism and mobile phone addiction strengthened via obsessive-compulsory behaviour (Index = 0.008, 95%CI [0.001, 0.004]). Conclusions This large-scale study revealed that individuals high in perfectionism and anxiety are vulnerable for mobile phone addiction, with compulsive use of mobile phone serving as a maladaptive coping strategy to manage distress. The findings contribute to an integrated model that incorporates personality traits, cognitive-behavioral processes, and emotional factors in the development of mobile phone addiction. Perfectionism-informed education and intervention is encouraged to prevent mobile phone addiction in education, clinical, and public health instances.